Total and Intratumoral CD8+ T Cell Expressions are Correlated with Miller Payne Grading and WHO Clinical Response of Neoadjuvant Chemotherapy - Sonar Soni Panigoro; Sinta Chaira Maulanisa; Ahmad Kurnia; Denni Joko Purwanto; Primariadewi Rustamadji; Herqutanto Herqutanto; Ferry Sandra (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Chemotherapy has reported to stimulate immune system through direct activation of cluster of differentiation (CD)8+ T cells. Neoadjuvant chemotherapy (NAC) is known to improve the clinical response of locally advanced breast cancer (LABC) patients. However, the immune response-related factor evaluation of NAC in LABC patients has not been routinely performed. Therefore, current study was conducted to evaluate the correlation of NAC-induced CD8+ T cell with chemotherapy response based on Miller Payne grading and World Health Organization (WHO) criteria.METHODS: LABC patients were recruited and data regarding age, gender, tumor, nodal stages, histopathological grade, estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2) and Ki67 were obtained. Biopsy and mastectomy tissues were collected and processed for hematoxylin-eosin and CD8 immunohistochemical staining. CD8+ T cell expression in peritumoral and intratumoral areas were documented and measured. Clinical responses based on Miller Payne grading and WHO were analyzed and correlated with CD8+ T cell expression.RESULTS: There were more subjects with high expression of total (80%), intratumoral (82.5%) and peritumoral (65%) CD8+ T cell expressions. The total (p=0.013) and intratumoral (p=0.015) CD8+ T cell expression, but not peritumoral CD8+ T cell expression, were significantly correlated with Miller Payne Grading. The total (p=0.009) and intratumoral (p=0.001) CD8+ T cell expressions were also significantly correlated with WHO clinical response.CONCLUSION: Total and intratumoral CD8+ T cell expressions are correlated with Miller Payne grading and WHO clinical response of NAC. Therefore, total and intratumoral CD8+ T cell expressions could be suggested as a predictive marker for clinical response of NAC.KEYWORDS: breast cancer, neoadjuvant chemotherapy, CD8, clinical response, Miller Payne, intratumoral, peritumoral